The optimal placement method of anchor nodes toward RSS-based localization systems - Rui Zhang; Weiwei Xia; Ziyan Jia; Lianfeng Shen; Jinghong Guo (2014 Sixth International Conference on Wireless Communications and Signal Processing (WCSP), 2014)
The needs for location-aware applications are increasing with the popularity of ubiquitous mobile computing. However, as an important factor affecting the positioning performance, the deployment of anchor nodes has received little attention during the past years. In this paper we investigate the anchor placement in the received signal strength (RSS) based wireless localization systems. An optimization method based on integer-coded genetic algorithm is proposed. It takes the average localization error and the signal coverage estimate as a joint optimization criterion. The influence of RSS fluctuation on the system is also considered in the algorithm. We evaluate the performance of our proposed algorithm in simulations and the results are discussed in details.